2007
DOI: 10.1103/physrevlett.98.027003
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities in the Vortex Matter and the Peak Effect Phenomenon

Abstract: In single crystals of 2H-NbSe2, we identify for the first time a crossover from a weak collective to a strong pinning regime in the vortex state which is not associated with the peak effect phenomenon. Instead, we find the crossover is associated with an anomalous history dependent magnetization response. In the dc magnetic field (Bdc)-temperature (T) vortex matter phase diagram we demarcate this pinning crossover boundary. We also delineate another boundary which separates the strong pinning region from a the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
33
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 25 publications
4
33
3
Order By: Relevance
“…The OD transition was suggested to be a thermodynamic phase transition induced by thermal fluctuations or pinning centers [2], which has been confirmed experimentally by the direct structural observation of the vortex lattice, such as small angle neutron scattering (SANS) [9], and muon spin relaxation [17]. Also, the investigation of the reversibility of the OD transition provided strong support for its thermodynamical nature [18].However, the exact nature of the PE phenomenon remains controversial [6,7,10,[19][20][21]. Recently, across the PE regime no noticeable change in the order of the vortex lattice was observed by SANS [19], and by Bitter decoration [20].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…The OD transition was suggested to be a thermodynamic phase transition induced by thermal fluctuations or pinning centers [2], which has been confirmed experimentally by the direct structural observation of the vortex lattice, such as small angle neutron scattering (SANS) [9], and muon spin relaxation [17]. Also, the investigation of the reversibility of the OD transition provided strong support for its thermodynamical nature [18].However, the exact nature of the PE phenomenon remains controversial [6,7,10,[19][20][21]. Recently, across the PE regime no noticeable change in the order of the vortex lattice was observed by SANS [19], and by Bitter decoration [20].…”
mentioning
confidence: 99%
“…Recently, across the PE regime no noticeable change in the order of the vortex lattice was observed by SANS [19], and by Bitter decoration [20]. It was also reported that the PE is situated on a boundary separating the strong pinning regime from the thermal fluctuations dominated regime, while the weak-strong pinning crossover is located far from the PE regime [7]. On the other hand, for some superconductors with strong pinning centers, it has been found that the occurrence of the PE depends strongly on the strength and amount of the pinning centers [3,6,22,23].…”
mentioning
confidence: 99%
See 3 more Smart Citations